2020
DOI: 10.1007/s10668-020-00740-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 virus outbreak lockdown: What impacts on household food wastage?

Abstract: The 2019-2020 coronavirus disease (COVID-19) is a public health issue. Lockdown is among options suggested to reduce spread of the virus. This study aimed to determining the impact of COVID-19 lockdown on Tunisian consumer awareness, attitudes and behaviors related to food wastage. An online survey was conducted during the first 2 weeks of COVID-19 lockdown. The survey collected information on demographic data, awareness and attitudes toward food waste, food purchase behavior and household food expenditure est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
449
12
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(558 citation statements)
references
References 22 publications
(62 reference statements)
64
449
12
10
Order By: Relevance
“…Environmental researchers have likewise focused on the lockdown impact on changes of energy consumption, waste management and daily habits among citizens. Jribi et al (2020) , for example, assessed the effect of the lockdown on Tunisian consumer awareness, attitudes and behaviors related to food wastage. Their findings indicate that the COVID-19 lockdown improved food shopping performance and pushed toward a positive behavioral change with regard to food wastage: 85% of the respondents declared that none of their purchases were discarded.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental researchers have likewise focused on the lockdown impact on changes of energy consumption, waste management and daily habits among citizens. Jribi et al (2020) , for example, assessed the effect of the lockdown on Tunisian consumer awareness, attitudes and behaviors related to food wastage. Their findings indicate that the COVID-19 lockdown improved food shopping performance and pushed toward a positive behavioral change with regard to food wastage: 85% of the respondents declared that none of their purchases were discarded.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we did not observe any increase in the consumption of health-promoting products recommended by the Food and Nutrition Institute (currently a part of the National Institute of Public Health, National Institute of Hygiene) such as vegetables and fruit or pickled food, low-fat dairy products [ 33 ]. Consumer behavior evaluated in a Tunisian study showed that 89% of the respondents declared to be aware of food waste, and the COVID-19 lockdown would impact 93% of them; their waste levels; and, for 80%, their grocery shopping habits [ 34 ]. Significant reductions in the frequency of the consumption of fast-food products ( p = 0.0001) and instant soups or ready-made jars ( p = 0.0247) were among the positive changes observed due to lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Water pollution are also reduced in the beach areas of Bangladesh, Malaysia, Thailand, Maldives, and Indonesia (Kundu, 2020;Rahman, 2020). Jribi et al (2020) reported that, due to the COVID-19 lockdown, the amount of food waste is reduced in Tunisia, which ultimately reduces soil and water pollution. However, the amount of industrial water consumption is also reduced, especially from the textile sector around the glove (Cooper, 2020).…”
Section: Reduction Of Water Pollutionmentioning
confidence: 99%